Comparison of the Efficacy and Safety of Minimally Invasive Simple Prostatectomy and Endoscopic Enucleation of Prostate for Large Benign Prostatic Hyperplasia - Li, Jinze; Cao, Dehong; Meng, Chunyang; Xia, Zhongyou; Peng, Lei; Li, Yunxiang; Wei, Qiang (Frontiers in Medicine, 2021)
Background: Minimally invasive simple prostatectomy (MISP) and endoscopic enucleation of the prostate (EEP) are the two most commonly used methods for large benign prostatic hyperplasia (BPH), but it remains unclear which of the two is superior. This study aims to perform a meta-analysis to compare efficacy and safety profiles between MISP and EEP. Methods: We conducted a comprehensive search of PubMed, Embase, Web of Science, and ClinicalTrials.gov databases to identify eligible studies comparing MISP with EEP. Parameters including efficacy and safety outcomes were compared using Stata 14.0 version. Results: Eight comparative trials with 1504 patients were included. Compared to MISP, EEP demonstrated shorter operative time (mean difference [MD] 46.37, 95% confidence interval [CI] 19.92 to 72.82, p = 0.0006), lesser hemoglobin (Hb) decrease (standardized MD [SMD] 0.59, 95% CI 0.23 to 0.95, p = 0.001), lower catheterization time (SMD 4.13, 95% CI 2.16 to 6.10, p < 0.001), and shorter length of stay (LOS) (SMD 2.38, 95% CI 1.40 to 3.36, p < 0.001). However, overall complications and blood transfusions did not differ between the two groups. Moreover, EEP had better postvoid residual volume (PVR) at 6-month (MD 14.39, 95% CI -9.73 to 7.30, p = 0.78) and comparable 3- and 6-month International Prostate Symptom Score, 3- and 6-month maximum flow rate, 3-month PVR, and 3-month quality of life compared with MISP. Conclusion: Both MISP and EEP are effective and safe surgical procedures for the treatment of large BPH. EEP appears to have a superior perioperative profile compared to MISP. This should be interpreted with caution due to the significant heterogeneity between studies. Hence, treatment selection should be based on the surgeon's experience and availability.